A histopathological study of the geoduck clam Panopea abbreviata from San José Gulf, North Patagonia, Argentina - Vázquez, Nuria Natalia (2015)
This is the first study performed to determine the health status of the geoduck Panopea abbreviata in the San Jose ́ and San Matı ́ as Gulfs (North Patagonia, Argentina). The study was based on 120 geoducks collected (30 specimens in each season) at Fracasso Beach (42 8 25 ′ S64 8 07 ′ W) (San Jose ́ Gulf) and 30 specimens collected during the austral summer at Puerto Lobos (42 8 00 ′ S65 8 05 ′ W) (San Matı ́ as Gulf). The parasites found (prevalence in parentheses) were: prokaryotic inclusions (32.2%) were recorded in the epithelium of the digestive gland and gill filaments; ciliates (79%) mainly found in gills; Porospora -like gregarines (15.2%) in the connective tissue between inner and outer mantle epitheliums; the turbellarian Paravortex panopea (27.1%) in the intestine lumen; the nemertean Malacobdella arrokeana (98.3%) in the pallial cavity; and the green alga Coccomyxa parasitica (51%) parasitizing the haemocytes in the connective tissue of the distal end of the siphon. The highest mean parasitic abundance value was found in the late austral spring (November), coinciding with the lowest values of the condition index of the host. The populations of P. abbreviata from San Jose ́ Gulf seemed to be devoid of severe pathogens.